Unusual {⋯HNC2O⋯HCnO}, n = 1 or 2, synthons predominate in the molecular packing of one-dimensional coordination polymers, {Cd[S2P(OR)2]2(3LH2)}n, for R = Me and Et, but are precluded when R = i-Pr; 3LH2 = N, N′-bis(3-pyridylmethyl)oxalamide. Issue 16 (28th March 2022) - Tan, Yee Seng; Yeo, Chien Ing; Kwong, Huey Chong; Tiekink, Edward R. T.
Abstract : The electronic & steric influence of the dithiophosphate-R groups mediates the formation of unprecedented supramolecular synthons. Abstract : Linear, one-dimensional coordination polymers, {Cd[S2 P(OR)2 ]2 ( 3 LH2 )} n, for R = Me (1 ), Et (2 ) and i-Pr (3 ) have been fully characterised by a variety of physiochemical, spectroscopic, crystallographic and computational techniques. Two-dimensional layers are apparent in the crystals of 1 and 2, being mediated, respectively, by unusual {⋯HNC2 O⋯HC n O}, n = 1 or 2, synthons formed between the oxalamide and phosphorus-bound alkoxy residues. Related synthons are not observed in the crystal of 3, with supramolecular tapes, mediated by concatenated {⋯HNC2 O}2 synthons, being formed instead. The observed differences in supramolecular association are ascribed to the increased steric bulk and reduced inductive effect of the R = i-Pr group compared with R = Me and Et.